Identifying the Theoretical Review of Narrow Free Voluntary Web-surfing for Reading Comprehension and Reader’s Interest - Rose Agustina; Ali Mustofa; Him’mawan Adi Nugroho (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The theoretical research aim is to investigate statements written by Stephen Krashen in his book Free Voluntary Reading about the use of Narrow FVS (free voluntary web-surfing) in reading and its potential to foster reading interest, motivation, and understanding of readers. Based on the literature review analysis, several points can be obtained that will make it easier for readers to develop their language skills and make them useful to understand a text. Kindly separate the rationale of narrow FVS, including narrow reading, free voluntary reading, and free voluntary web surfing, all three of which can be concluded to have good potential in making it easier for readers to understand a reading text, get varied input material easily, and be a good solution for growing reading habits. The research can be concluded from several analyses of the three techniques, which have the same characteristics, including extensive reading and pleasure reading, so they can be combined. In addition, reducing reading lexical load and anxiety will positively impact readers' motivation to continue reading in large quantities with more confidence